Makna Tradisi Mbecek dalam Perkembangan Budaya Masyarakat Karanggayam - Umi Hanik (Asketik)
This study aims to explain the socio-religious changes of the Karanggayam community in the tradition of mbecek, celebration, circumcision, birth of a baby, the dead and the sick.tradition mbecek is a tradition handed down by the ancestors of the Karanggayam community which is still being preserved and maintained, the pattern used for religious encouragement and ashabiah namely the Rukun Tetangga (RT) environment. This research is qualitative research with a phenomenological approach that focuses on socio-religious changes in the muddy. Data collection techniques used were interviews in Karanggayam village with data analysis methods, namely data presentation, data reduction and drawing conclusions. From the results of this study, it can be concluded that there are two forms of change, namely, first changes in exchange practices that are recorded in the mbecek celebration system, and secondly forms ashabiah tradition mbecek micro-religious